Asthma care during pregnancy in South Asia - Piryani, Rano Mal; Piryani, Suneel; Sijapati, Milesh Jung; Karthak, Ashish (Nepalese Respiratory Journal, 2023)
Bronchial asthma is among the commonest chronic inflammatory respiratory diseases affecting women of reproductive age group. Adequate attention has not been given to the diagnosis and the management of asthma in countries of South Asia. Management of asthma in pregnant women is more or less same as that of in non-pregnant women and stepwise approach is recommended. To confirm the diagnosis of asthma during pregnancy, spirometry can be used. Patients suffering from very severe asthma or difficult-to control asthma are more prone to develop exacerbations during pregnancy needs hospitalization for care. Well-controlled asthma during pregnancy prevents complications of pregnancy and results in better pregnancy outcomes. It better to follow the guidelines for management of asthma during pregnancy. The pregnant women must be educated regarding the care of asthma during pregnancy, delivery, in postpartum period and thereafter.